Urgensi Pemimpin Adil dan Berpengetahuan Luas: Perspektif Anies Baswedan - Siti Habibah khumalia; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
The study aims to find out how to be a fair and knowledgeable leader. This report uses a qualitative descriptive method by listening closely because the data source was obtained by listening to the oral narrative from the CXO Media YouTube channel entitled